Development of Weebly-Based Website Learning Media Containing Ethnochemical Acid-Base Material - Irnawati Irnawati; Setia Rahmawan (IKIP Mataram, 2024)
Technological disruption causes relatively rapid and even uncontrollable social change, while the pace of education moves at a super slow speed. Weebly is an alternative media technology that can be used as a learning medium. This research aims to produce Weebly-based learning media that contains ethnochemistry that is valid and suitable for use in the learning process and as a student learning resource. Weebly-based learning media is an innovation that teachers can use to facilitate the learning process through presenting culture related to chemistry on the website. This research uses an R&D approach with the ADDIE model. The instruments used in this research were validation sheets and product assessment sheets. The product was validated by one material expert and one media expert and assessed by three chemistry teachers and thirty high school students. The expert validation results show that the learning media is very valid in terms of material and media. The results of the learning media assessment by three chemistry teachers obtained an average score of 110.3 with a percentage of 91.9% in the very good category. Student responses to the learning website were also positive with an ideal percentage of 96.7% in the very good category. The results of expert validation, teacher assessments, and student responses show that the website is valid to use as a chemistry learning medium and as a learning resource.